Coagulation of turbid waters using extraction of long bean - A.G, Liew,; M.J.M.M, Noor,; Y.M., Ng, (Malaysian Journal of Science, 2004)
Coagulation is an important process in water treatment. The common chemical coagulant used in the water treatment is alum (aluminium sulphate). However, since the publicity of Moringa Oleifera seed as natural coagulant, researchers have tried to exploit the possible usage of natural coagulants as well as developing new natural coagulants from other plants. The potential of a locally available vegetable, long bean, to act as natural coagulant was studied using jar test. Synthetic turbid water used was prepared by adding kaolin to distilled water. It was discovered that long bean extract alone could not remove the turbidity. However, the coagulation activity was remarkable only when bivalence cation such as Cal* and Mn2 were added. In this study, the active component of long bean was extracted using sodium chloride solution. The long bean extract achieved an average turbidity removal efficiency of 80 %.